Perlindungan Pendapatan Daerah dari Pembayar Pajak Kendaraan yang Mangkir Perspektif Maqashid Syariah - Ningrum, Dewa Alyu Sastra; Zulham, Zulham (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to determine the protection of Regional Income from vehicle taxpayers who are absent from the perspective of Maqashid Syariah at the SAMSAT Office. Motor vehicle tax is a fairly large source of income, but some people are still not compliant with tax payments, so that vehicle owners' tax compliance is not optimal. In implementing the Regional Regulation of North Sumatra Province Number 6 of 2018 concerning Regional Taxes, it is also necessary to establish guidelines and procedures for collecting motor vehicle taxes as stated in the Regulation of the Governor of North Sumatra Number 12 of 2019. This study aims to determine the potential income of the Binjai City Government from vehicle taxpayers who are absent, the impact of motor vehicle taxpayers who are absent, and the protection of Regional Income from vehicle taxpayers who are absent when viewed from the perspective of Maqashid Syariah. This type of research is empirical legal research with a statute approach and living case studies. From the perspective of Maqashid Syariah, efforts to protect Regional Income related to motor vehicle taxpayers are the application of the Maqashid Syariah principle, so it is mandatory to protect Regional Income and comply with the payment of motor vehicle taxes.